Post-Translational Modifications in Cellular Functions and Diseases - Ying, Shibo (IntechOpen, 2021)
Post-Translational Modifications (PTMs) may occur at any stage following the translation process in the lifecycle of specific proteins. PTMs regulate several cellular processes including protein stability, subcellular localization, and protein-protein interactions. In recent years, more and more target proteins of PTMs have been proved to be related to epigenetic regulation and cell fate. Some enzymes that catalyze PTMs have also been found to be involved in human diseases. This book intends to provide the reader with an overview of the current state of the art in this research field, which focuses on the recent advances, new findings and perspectives in cellular functions, and their clinical significance in human diseases. We hope this book will help researchers in this area.